MANIFESTATION OF FREEDOM OF SPEECH REFORM THROUGH EFFORTS TO STRENGTHEN ONLINE PETITIONS IN THE PROCESS OF FORMING AND MONITORING GOVERNMENT POLICIES - Naila Ammara; Muhammad Fikri Ihsani; Kuntum Khaira Sado (Journal of Governance and Law Reform, 2026)
ABSTRACT The freedom to express opinions including through online petitions, is an obligation that must be guaranteed by the government, as mandated by regulations across various sectors. However, there are several issues in its implementation due to limited regulatory substance, weak government intervention, and the absence of monitoring and evaluation mechanisms for online petitions. As a result, many online petitions go unanswered by the government. This situation demonstrates the need to re-evaluate policies on freedom of expression through online petitions. This study aims to analyze the urgency of institutionalizing online petitions as a form of freedom of expression in government administration and to provide strategies for implementing and formulating the institutionalization of online petitions to achieve freedom of expression reform in Indonesia. This writing employs a normative juridical method using legislative, conceptual, comparative, and case approaches. Based on the research findings, the author proposes a mechanism for supervising online petitions through the Ombudsman to optimize the government's role in monitoring and evaluating the implementation of online petitions. Optimization is carried out by drafting specific regulations as guidelines for the government and the public to ensure freedom of expression through online petitions. The presence of this mechanism is expected to resolve the issues in the implementation of online petitions in Indonesia, thereby achieving freedom of expression reform through the institutionalization of online petitions.